Radon and Thoron Exhalation Rates from Surface Soil of Bangka - Belitung Islands, Indonesia - Syarbaini, Syarbaini; Pudjadi, E. (Geological Agency, 2015)
DOI:10.17014/ijog.2.1.35-42Radon and thoron exhalation rate from soil is one of the most important factors that can influence the radioactivity level in the environment. Radon and thoron gases are produced by the decay of the radioactive elements those are radium and thorium in the soil, where its concentration depends on the soil conditions and the local geological background. In this paper, the results of radon and thoron exhalation rate measurements from surface soil of Bangka Belitung Islands at thirty six measurement sites are presented. Exhalation rates of radon and thoron were measured by using an accumulation chamber equipped with a solid-state alpha particle detector. Furthermore, the correlations between radon and thoron exhalation rates with their parent nuclide (226Ra and 232Th) concentrations in collected soil samples from the same locations were also evaluated. The result of the measurement shows that mostly the distribution of radon and thoron is similar to 226Ra and 232Th, eventhough it was not a good correlation between radon and thoron exhalation rate with their parent activity concentrations (226Ra and 232Th) due to the environmental factors that can influence the radon and thoron mobilities in the soil. In comparison to a world average, Bangka Belitung Islands have the 222Rn and 220Rn exhalation rates higher than the world average value for the regions with normal background radiation.